2007
DOI: 10.1108/14757700710725458
|View full text |Cite
|
Sign up to set email alerts
|

Earnings management and board activity: an additional evidence

Abstract: Purpose -The purpose of this paper is to examine the relation between earnings management behavior and the activity of both the board and audit committee. Design/methodology/approach -Different models to isolate abnormal accruals as a proxy for earnings management are applied to a sample of manufacturing companies. Findings -Earnings management is negatively related to both board and audit committee independence. Such negative relation is stronger when the audit committee is more active. However, this result i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
116
3
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(138 citation statements)
references
References 41 publications
12
116
3
7
Order By: Relevance
“…The "efficient monitoring hypothesis" could be the best explanation of our findings (e.g. Almazan et al, 2005;Bange & De Bondt, 1998;Bushee, 1998;Chung et al, 2002;Cornett et al, 2008;Ebrahim, 2007;Koh, 2003).…”
Section: Findings and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The "efficient monitoring hypothesis" could be the best explanation of our findings (e.g. Almazan et al, 2005;Bange & De Bondt, 1998;Bushee, 1998;Chung et al, 2002;Cornett et al, 2008;Ebrahim, 2007;Koh, 2003).…”
Section: Findings and Discussionmentioning
confidence: 98%
“…As a result, institutional ownership and companies' earnings management activity is inversely related (e.g. Almazan, Hartzell, & Starks, 2005;Bange & De Bondt, 1998;Bushee, 1998;Chung, Firth, & Kim, 2002;Cornett, Marcus, & Tehranian, 2008;Ebrahim, 2007;Koh, 2003). Conversely, the second hypothesis suggests that institutional ownership may not limit managers' earnings management activity and may increase their incentives to engage in earnings management.…”
Section: Institutional Ownership and Earnings Managementmentioning
confidence: 94%
“…In addition, other studies (Brickley, Coles & Terry, 1997;McWilliams & Sen, 1997) support the expectation that boards will be effective in helping to protect shareholders' wealth if they have a higher proportion of outside directors because outside directors can make independent judgments uninfluenced by management and opportunities. However, other studies (Chtroutou, Bedard & Courteaul, 2001;Park & Shin, 2004;Ebrahim, 2007) have yielded inconsistent results about earnings management and the independence of directors. This could have been due to the limited availability of information www.ccsenet.org/ijef International Journal of Economics and Finance Vol.…”
Section: Independence Of the Board Of Directorsmentioning
confidence: 96%
“…Jiang et al (2010) found that the magnitude of accruals and the likelihood of beating analyst forecasts are more sensitive to CFO equity incentives than to those of the Chief Executive Officer (CEO). Although a significant amount of accounting research has been devoted to testing the association between the effectiveness of corporate governance and audit committees on earnings management (Lin and Hwang 2010;Benkraiem 2009;Ebrahim 2007;Xie et al 2003;Klein 2002), only a few studies have examined the association between gender diversity on the board of directors and earnings management. For instance, Barua et al (2011) investigated the association between CFO gender and earnings management and found that firms with female CFOs have lower discretionary accruals than firms with male CFOs.…”
Section: Female Directors and Earnings Management -The Key Questionsmentioning
confidence: 99%